Electronic publications of archival institutions in the Republic of Kazakhstan and features of the developed Е-Doc Complex website - Zhakupova, Gulnaziya T.; Sydykova Aigerim А.; Donninghaus, Victor; Elle, Venera Zh. (The New Research of Tuva, 2024)
At the present time, electronic publication of archival documents is a modern high-profile way to use them and satisfy information needs of the society and researchers, as well as to popularize the documentary heritage. Publications of archival institutions on the Internet imply a multi-faceted practice, which includes development of search tools and reference mechanisms for collections, providing digital copies of archival documents on certain topics. Archival institutions create various types of electronic publications, namely databases, online exhibitions, collections of archival materials. Thus, currently, electronic archaeography is a promising research area due to the active advancements in the discipline’s practical applications. Publication of collections of archival documents is the most problematic issue among all types of documentary publication in electronic form. The purpose of the article is to analyze the main types of documentary publications provided by archival institutions in the digital environment and to reveal the specifics of the developed software product for publishing collections of archival materials. The research uses materials from the state archives of the Republic of Kazakhstan, regulatory and methodological documents. The results of the research include the following: an analysis of the academic discourse on the problems of publishing documentary heritage at the present stage was carried out; types of electronic publications and methods of their creation in the digital space were examined using the example of the state archives of the Republic of Kazakhstan; the E-Doc Complex website was developed as a separate software product for creating three types of collections of archival documents and thematic virtual exhibitions.